The role of self-conscious emotions in ethical consumption - Gregory-Smith, Ioana Diana (2012)
This thesis examines the role of self-conscious emotions (SCEs) in ethical consumption. The work is primarily psychological and it seeks to add to the generic literature on the role of emotions in consumer behaviour by focusing on SCEs, such as guilt and pride, and analyses their special place in ethical consumption decisions. A mixed method approach was adopted, combining a qualitative study and a quantitative experiment.